2018
DOI: 10.1186/s12885-018-4353-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term fasting on quality of life and tolerance to chemotherapy in patients with breast and ovarian cancer: a randomized cross-over pilot study

Abstract: BackgroundThis pilot trial aimed to study the feasibility and effects on quality of life (QOL) and well-being of short-term fasting (STF) during chemotherapy in patients with gynecological cancer.MethodsIn an individually-randomized cross-over trial patients with gynecological cancer, 4 to 6 planned chemotherapy cycles were included. Thirty-four patients were randomized to STF in the first half of chemotherapies followed by normocaloric diet (group A;n = 18) or vice versa (group B;n = 16). Fasting started 36 h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
261
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(290 citation statements)
references
References 19 publications
11
261
2
16
Order By: Relevance
“…Thus, we also conducted a systematic review of experimental studies investigating the effect of dietary interventions, alone or in combination with other recommendations, on the QoL of breast cancer survivors. Although all the studies underlined significant improvements in QoL after the interventions, only a trial evaluated the sole and exclusive effect of dietary intervention [47]. The rest of studies, instead, combined the promotion of dietary recommendations with programs aiming to increase exercise and physical activity among breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we also conducted a systematic review of experimental studies investigating the effect of dietary interventions, alone or in combination with other recommendations, on the QoL of breast cancer survivors. Although all the studies underlined significant improvements in QoL after the interventions, only a trial evaluated the sole and exclusive effect of dietary intervention [47]. The rest of studies, instead, combined the promotion of dietary recommendations with programs aiming to increase exercise and physical activity among breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only the single-arm trial by Bauersfeld and colleagues evaluated the effect of an intervention based exclusively on dietary recommendations. They demonstrated that short-term fasting followed by normo-caloric diet counteracted the reduction of QoL in the first half of chemotherapy [47]. Specifically, the reduction in QoL after chemotherapy was less than the minimally important difference with short-term fasting but greater than the minimally important difference for non-fasted periods.…”
Section: Findings From the Systematic Reviewmentioning
confidence: 99%
“…Some studies have suggested a short-term but more extreme food restriction, especially prior to treatment with chemotherapy, immunotherapy, or other targeted agents, with the goal of enhancing the anti-cancer effects of the therapy to allow patients to benefit from the diet without the negative effects associated with long-term exposure to that diet 12,69,70 . Indeed, several clinical trials have been initiated to explore these dietary strategies [71][72][73][74] . Whether changes to lipid availability and metabolism, as well as other metabolic alterations, contribute to the effects of these short-term dietary interventions is an area for further exploration.…”
mentioning
confidence: 99%
“…Similarly to Bauersfeld et al(10), we collected data on QoL, fatigue and additionally CIPN. While Bauersfeld et al(10) observed significant improvements in fatigue and QoL due to STF during chemotherapy, our results were not able to confirm these findings.…”
mentioning
confidence: 99%
“…Similarly to Bauersfeld et al(10), we collected data on QoL, fatigue and additionally CIPN. While Bauersfeld et al(10) observed significant improvements in fatigue and QoL due to STF during chemotherapy, our results were not able to confirm these findings. However, it should be noted, that the informative value of the three above mentioned questionnaires is limited due to an unfavourable point in time for data collection on the day of chemotherapy, reflecting QoL, CIPN and fatigue in the week before chemotherapy.…”
mentioning
confidence: 99%